2022
DOI: 10.4236/psych.2022.139092
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy Predictors of Consistent Condom Use among an Ethnically and Racially Diverse Sample of Young Adults

Abstract: Background: Condom use can decrease the likelihood of acquiring STIs. Condoms are more efficacious when used consistently and correctly. However, low percentages of consistent condom use have been reported by adults and young adults, with consistent condom use decreasing with age. Furthermore, there are racial/ethnic differences in both condom use and STI incidence. Self-efficacy has been found to be positively related to condom use, and various domains of self-efficacy have been studied in previous research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Consistent with this, a study conducted in a minority-serving institution in the United States discovered that those who reported being able to put on or have their partner(s) put on a condom without ruining the mood were 7.7 times more likely to be a consistent condom user. 28 Previous research discovered that self-efficacy for condom negotiation and preparatory safer sexual behaviour were significantly associated with consistent condom usage, as was abstinence, implying that women who exhibit this behaviour are more likely to use condoms. 29 As condom use self-efficacy was associated with consistent condom use, higher education institutions should introduce programmes and activities that promote increased selfefficacy, self-esteem and sexual reproductive health and well-being in young women.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, a study conducted in a minority-serving institution in the United States discovered that those who reported being able to put on or have their partner(s) put on a condom without ruining the mood were 7.7 times more likely to be a consistent condom user. 28 Previous research discovered that self-efficacy for condom negotiation and preparatory safer sexual behaviour were significantly associated with consistent condom usage, as was abstinence, implying that women who exhibit this behaviour are more likely to use condoms. 29 As condom use self-efficacy was associated with consistent condom use, higher education institutions should introduce programmes and activities that promote increased selfefficacy, self-esteem and sexual reproductive health and well-being in young women.…”
Section: Discussionmentioning
confidence: 99%
“…Although the research team did not state that all the targeted HIV prevention methods needed to be used concurrently, this may have contributed to AYAs' attitudes toward using multiple methods as being "too much" to do. Other studies have found that AYAs are less likely to use individual HIV prevention methods if the ability to carry out uptake is seen as being too cumbersome (Carmack et al, 2022). Thus, perceptions that using more than one HIV prevention method is too much to do could significantly affect initial or consistent uptake of CHPMs.…”
Section: Perceived Feasability Of Using Combination Hiv Prevention Me...mentioning
confidence: 99%